2016
DOI: 10.18632/oncotarget.10055
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive immunohistochemical analysis of tumor microenvironment immune status in esophageal squamous cell carcinoma

Abstract: Immunotherapy with anti-PD-1 antibody preliminarily showed promising efficacy for treating esophageal squamous cell carcinoma (ESCC). Herein, we used tissue microarrays and immunohistochemically analyzed PD-L1 and various tumor infiltrating immune cells (TIICs) in specimens from 196 ESCC patients who had undergone curative resection without preoperative therapy. PD-L1 expressions in tumor cells (TCs) and TIICs, as well as infiltration of lymphocytes (CD4+, CD8+, FOXP3+, and PD- 1+) and macrophages (CD68+ and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
84
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 55 publications
16
84
3
Order By: Relevance
“…Data from evaluation of tumours in other organs, such as the breast and oesophagus, are not dissimilar from ours, and stress the importance of immune microenvironment evaluation in a broad range of tumour types. In their review, Taube et al .…”
Section: Discussionmentioning
confidence: 40%
“…Data from evaluation of tumours in other organs, such as the breast and oesophagus, are not dissimilar from ours, and stress the importance of immune microenvironment evaluation in a broad range of tumour types. In their review, Taube et al .…”
Section: Discussionmentioning
confidence: 40%
“…No reports on tumor‐infiltrating CD8 + T cells, CD4 + T cells, or TAMs in cervical adenocarcinoma have yet been published. We showed that CD204 + TAMs were associated with poorer prognosis, as in most solid tumors . Tumor‐associated macrophages promote tumor progression or certain forms of malignant phenotypes, such as tumoral invasion and metastasis at the invasive edge .…”
Section: Discussionmentioning
confidence: 85%
“…In contrast to the control group, there existed statistical significance. It is suggested that the pathogenic factors involved in promoting leukemia cell exaggerated proliferation, differentiation blocked, and apoptosis resistance still existed, so the therapy strategy of CML needed to combine with modification bone marrow (BM) homeostasis [5, 36]. …”
Section: Discussionmentioning
confidence: 99%